PENGUJIAN KUALITAS SOAL ETIKA PROFESI KEUANGAN SEBAGAI ALAT EVALUASI PEMBELAJRAN KELAS X MELALUI UJI ANATES VERSI 4.0 - MUDIYANTRI, NOVA SIXCA; INDRIANI, NADYA SHAFIRA; NARISWARI, FASYA ANINDYA; FADILAH, VIVI NUR; NOVITASARI, DUWI PUTRI; HAKIM, LUQMAN; PRATIWI, VIVI (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to assess the feasibility of multiple-choice questions on the topic of Professional Ethics in Finance and Accounting, which are compiled based on modules and e-books, and then tested online via Google Forms to 10th-grade high school and vocational high school students. The assessment covers four main aspects: validity, reliability, discriminatory power, and difficulty level using Anates software. A total of 25 students participated as respondents through a test designed according to the basic competencies in the professional ethics material. The analysis results show that the reliability of the questions is in the very high category with a value of 0.92. In terms of validity, the majority of the questions are in the very high category, followed by a small number in the high, low, and very low categories. The discriminatory power shows a variety of quality from very good to needing revision. The level of difficulty is generally in the moderate category, with some questions categorized as easy, very easy, and difficult. The distractor evaluation also indicates that there are answer options that are not functioning optimally. Overall, this instrument is considered suitable for use, although several components still need improvement to be able to measure students' abilities more accurately.